Thrombolysis as first-line therapy for Medtronic/HeartWare HVAD left ventricular assist device thrombosis. (12th September 2020) - Dimitrov, Kamen; Maier, Julian; Sandner, Sigrid; Riebandt, Julia; Wiedemann, Dominik; Moayedifar, Roxana; Schlöglhofer, Thomas; Angleitner, Philipp; Niederdöckl, Jan; Schima, Heinrich; Tschernko, Edda; Laufer, Guenther; et al.
Abstract: OBJECTIVES: We reviewed our institutional experience with intravenous thrombolysis (TL) as first-line therapy in patients with Medtronic/HeartWare HVAD left ventricular assist device pump thrombosis (PT). METHODS: From March 2006 to November 2018, 30 Medtronic/HeartWare HVAD left ventricular assist device patients had 48 PT events. We analysed outcomes with intravenous Alteplase as a first-line therapy for PT. Pump exchange or urgent heart transplantation was only considered after the failure of TL or existing contraindications to TL. RESULTS: TL was used as the first-line therapy in 44 PT events in 28 patients without a contraindication to TL. TL was successful in 61.4% of PT events. More than 1 cycle of TL was necessary in 55.6% of events. The combined success of TL and heart transplantation or device exchange was 81.8%. In 15.9% of events, PT was fatal. Causes of death were severe complications (9.1%) related to TL or discontinuation of therapy for multi-organ failure (6.8%). Intracranial bleeding and arterial thromboembolism were observed in 4.5% and 11.5% of the PT events after TL. CONCLUSIONS: Intravenous TL as a first-line therapy for PT in Medtronic/HeartWare HVAD patients can be a reasonable treatment option and does not preclude subsequent heart transplantation or device exchange. However, thromboembolic and bleeding complications are common. The decision to perform TL or device exchange should, therefore, be made on an individual basis after balancing the risks and benefits of different treatment approaches.